Pengawasan terhadap Transaksi Bisnis E-Commerce dalam Mewujudkan Perlindungan Konsumen - Anak Agung Made Ayu Rai Lidya Astari; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2020)
E-commerce is a buying and selling activity carried out via the internet with electronic media. Based on this, two problems were raised as follows: 1). What are the aspects of consumer protection against electronic business transactions, 2). How to regulate the control of electronic business transactions in ensuring the implementation of consumer rights. The research method used in the preparation of this research is normative with a statutory approach and a conceptual approach, namely analyzing the problems to be discussed through legal concepts taken from several books and literature that have relevance to the problem. The data sources used are primary data, namely through statutory regulations, secondary data, namely using legal theory and experts, and tertiary data, namely related to legal dictionaries and encyclopedias. The technique of collecting data is through the method of recording legal materials and collecting references used. The data analysis used systematic legal interpretation and legal argumentation based on deductive logic. However, all the benefits that are offered, there is a concern about the responsibility of online companies to online consumers considering so many online companies. The Trade Law and the Consumer Protection Act are the basis for trading in online trading and / or in conventional trading. In this case the need for supervision in order to improve harmony in each application. The results showed that the aspect of protection was carried out by defending the rights of consumers against the disturbance of other parties. In order to increase awareness, knowledge, concern and independence of consumers, especially in choosing, determining and demanding their rights as consumers. There are several principles in consumer protection, namely the principle of benefit, the principle of justice, the principle of security and safety, the principle of balance, the principle of legal certainty.